Delayed recruitment of lymphocytes into the lungs of CD30-deficient mice during aerogenic Mycobacterium avium infections - Manuela Florido (2009)
CD30 is a member of the tumor necrosis factor-receptor superfamily, a group of receptors known to act as accessory molecules in the development of the immune response. Control and CD30-deficient mice were aerogenically infected with Mycobacterium avium. Although the mycobacterial loads in the lungs were similar in both strains of mice, CD30-deficient animals exhibited delayed structuring of pulmonary granulomas and reduced recruitment of lymphocytes throughout a 240 days period of infection. Discrete alterations in the chemokine network were detected in the CD30-deficient animals although they showed no clear relation to the deficient inflammatory response. Thus CD30/CD 153 interactions are involved in lung immune-mediated inflammation.